Endometriosis of Rectus Muscle Excised During Cesarean Section: A Case Report and Literature Review - Recep Erin; Kübra Baki Erin; Derya Burkankulu Ağırbaş; Burcu Kemal Okatan (Gynecology Obstetrics & Reproductive Medicine, 2017)
We aimed to present a case with abdominal wall endometriosis following cesarean section in this case report. A 32 year old 39 weeks pregnant woman with G2P1 was admitted to gynaecology clinic with abdominal lump and pain in the midline. Her physical examination included a hard and painful palpable subcutaneous mass of 4x5 cm size in the midline of the abdomen which was semisolid and irreducible. Under general anesthesia, the mass on the rectus muscle was excised with the healthy tissue around with the diagnosis of endometriosis during cesarean section and the pathological diagnosis was reported as endometriosis. Surgical excision is the best treatment method in abdominal wall endometriosis.